Estudo químico e avaliação da atividade antioxidante das substâncias isoladas da casca do caule e folhas de Eugenia dysenterica DC. (Myrtaceae) - Vitek, Renan (2013)
The family Myrtaceae, representing about 150 genera and 4,620 species and is distinguished by containing a large number of species with potential food. The Eugenia dysenterica DC. cagaita is popularly known as a fruit species native savannah and wetland Brazilian belonging to the family Myrtaceae. This is commonly indicated in folk medicine against dysentery, diabetes and jaundice. Phytochemical studies related to plants of this genus have reported the isolation of flavonoids, tannins, chalcones, polyphenols and constituents of essential oils and many of these compounds have shown biological activities. Thus, the indication popular in the treatment of diseases, the isolation of compounds from plants of the genus that are related to biological activities and the absence of phytochemical and pharmacological studies of Eugenia dysenterica, the aim of this work was the isolation and identification of the constituents of Eugenia dysenterica and evaluate the antioxidant activity by the DPPH method these isolated compounds. To obtain the compstos isolated the plant material , the stem bark and leaves collected at highway - Poconé Porto Cercado 8 km , city of Poconé / MT were cold macerated with methanol over a 7 day cycle , thus providing waste the peel hydroalcoholic stem and leaves . These were partitioned to obtain fractions with hexane ( Hex) , chloroform (CHCl3), ethyl acetate (EtOAc) , butanol (ButOH) and methanol (MeOH), respectively. The study led to the isolation of the sheets esters of 3-hydroxy-4-methoxy methyl (1), 4- hydroxyphenyl propionate methyl (2), E-methyl-4-hydroxycinnamate (3), 3-O-β- glucopyranosyl β-sitosterol (6) , all of these obtained from the chloroform fraction, and the flavonoid 3-O-β-galactopyranosyl quercetin (8) and quercetin 3-β-O-(6’’galloyl glycopiranosyl) (9) obtained from the ethyl acetate fraction . In the stem bark were identified acid 3-β-O-acetyl- olean-12-en-28 oic acid (4) acid and 3-acetyl-β-12-Ursen-28- oic acid (5) and the butanol fraction was isoquercetina (7) obtained. For structural determination techniques were used for 1H and 13C NMR (1D and 2D), IR and comparison with literature data. All samples tested had its antioxidant activity, but only for samples 7, 8 and 9 which are flanoidícos compounds showed high antioxidant power, which can be explained by the presence of the catechol ring in these compounds.